The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/evj.12470
|View full text |Cite
|
Sign up to set email alerts
|

Epiduroscopy of the lumbosacral vertebral canal in the horse: Technique and endoscopic anatomy

Abstract: Lumbosacral epiduroscopy is technically feasible in standing horses and may become a valuable diagnostic tool in horses with caudal back or limb pain of unknown origin. Studies in live horses will be necessary to evaluate the safety of the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Exclusion criteria were lameness at the walk and ataxia of greater than grade 1 . Furthermore, only horses with a minimum weight of 500 kg were enrolled as the diameter of the vertebral canal at the insertion site may not accommodate the 14 Fr introducer sheath that encloses the endoscope in smaller horses .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Exclusion criteria were lameness at the walk and ataxia of greater than grade 1 . Furthermore, only horses with a minimum weight of 500 kg were enrolled as the diameter of the vertebral canal at the insertion site may not accommodate the 14 Fr introducer sheath that encloses the endoscope in smaller horses .…”
Section: Methodsmentioning
confidence: 99%
“…A technique previously described in cadavers was used to enter and examine the lumbosacral epidural space with a flexible video‐endoscope . In brief, flexion and extension of the tail were used to identify the first moveable vertebral joint caudal to the sacrum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thank you for giving us the opportunity to respond to Dr. Josephson's letter, in which she clarifies an interesting aspect of the spinal nerve and nerve root anatomy in the lumbosacral epidural space. Interestingly, one reviewer addressed the same point during the submission process of our manuscript .…”
mentioning
confidence: 92%
“…In the article by T. Prange, et al , the authors identified the dura mater ‐enclosed structures within the horse's vertebral canal as spinal nerves. In fact, the long structures extending from their origin at the spinal cord nearly to their passage through an intervertebral foramen are dorsal and ventral spinal roots, not spinal nerves.…”
mentioning
confidence: 99%